BUSINESS INCOME AND NATIONAL INCOME: A CONTRAST OF CONCEPTS. - Maynard, Gilbert P. (The Accounting Review, 1952)
The purpose of this article is to set forth in rather elementary fashion some of the more fundamental differences between the business and national income concepts. The contrast of concepts is presented in terms of certain widely accepted standards and postulates underlying the measurement of business income. The national income accountant is concerned with the creation of product, not alone with its subsequent sale. The national income and product concepts are measures of output within the economy. Income is attributed to all productive processes and is not associated solely with the event of sale. National income is expressed in terms of the cost of the factors of production, while gross and net national product are measures of the market value of production. Thus a fundamental difference between enterprise and national income accounting lies in the difference in timing of recognition of revenue on the one hand and product on the other. Gains from exchanges of assets other than stock in trade are generally regarded as components of business revenue and are therefore given accounting recognition according to the same principles as other revenues. However, the realization of gain on the sale of a capital asset does not necessarily imply any contribution by the seller to the social product during the period of realization.